Cuban Adolescents Requesting Presymptomatic Testing for Spinocerebellar Ataxia Type 2. (30th April 2013) - Cruz-Mariño, Tania; Velázquez-Pérez, Luis; González-Zaldivar, Yanetza; Aguilera-Rodríguez, Raúl; Velázquez-Santos, Miguel; Vázquez-Mojena, Yaimé; Estupiñán-Rodríguez, Annelié; Laffita-Mesa, José Miguel; Reynaldo-Armiñán, Rubén; Almaguer-Mederos, Luis Enrique; Paneque, Milena
Abstract : Since 2001 a program for the presymptomatic testing of families affected with SCA2 has been under development in Cuba. According to the initial protocol, access would be given to nonsymptomatic individuals at 50% risk, over 18 years; nevertheless, eleven minors requested their inclusion in the program. A retrospective and descriptive study based on the analysis of the medical records belonging to these individuals was designed. Being aware of how challenging clinical settings of predictive genetic testing for minors are, this paper reviews their profile, the outcome of the carried out studies, as well as the reproductive option chosen by the gene positive consultands. The mean age at the time of testing was 16.2 years. Nine adolescents completed the protocol (three had positive test results) and two withdrew. They had a distinctive profile; all were females, pregnant, motivated by the risk assessment for their descendants, and interested in PND with termination of the gestation were the fetus a carrier. Nevertheless, once the result of the test is known, the gene positive consultands chose discordant reproductive options. Further research is necessary to assess the long-term psychological impact in both gene positive and gene negative participants, as well as in their parents and at-risk relatives.